Challenging diagnosis between intussusception and necrotizing enterocolitis in premature infants - TAŞKINLAR, HAKAN; Gundogdu, Gokhan; Celik, Yalcin; Avlan, Dincer; NAYCI, ALİ (My University, 2014)
Although necrotizing enterocolitis (NEC) is a frequently encountered entity in premature infants in the neonatal intensive care unit, intussusception is extremely rare. Abdominal distension, bilious/non-bilious gastric residuals and bloody stool are the common clinical findings of both entities. Here we present three cases of intussusception misdiagnosed as NEC, two of which were complicated with intestinal perforation. Similar clinical findings of NEC and intussusception leads to misdiagnosis and delay in treatment, particularly in premature infants with intussusception.